Past, present, and future perspectives of biodegradable films for soil: A 30-year systematic review - Sun, Yitao; Yang, Wenlong; Shi, Hongxia; Tanveer, Sikander Khan; Hai, Jiangbo (Frontiers in Bioengineering and Biotechnology, 2022)
Based on the Web of Science Core Collection (WOSCC) database, the academic works published in the past 30 years on biodegradable films for soil were analyzed. In order to ensure the rigor of this experiment, this paper is based on the mathematical double matrix model VOS Viewer software and CiteSpace software. This work shows that publications of biodegradable films for soil are increasing year by year; polymer science is the hottest subject in the field of biodegradable films for soil; China and the United States are the countries with the most significant number of publications in this field, has an important position; Washington State University is the most published institution. This study further identifies and reveals the essential characteristics, research strength, knowledge structure, main research fields, and research hotspots in the late stage of the field of biodegradable films for soil and introduces the Activity Index (AI) and the Attractive Index (AAI), thereby assessing trends and performance in different countries. The paper also further illustrates the importance of biodegradable films by presenting field trials using biodegradable films on different plants. The research in the field of biodegradable films for soil is divided into four categories: “The research field of degradation,” “The effect of biodegradable film on soil,” “Performance and mechanism of the biodegradable film,” and “Effects of biodegradable film on crop growth and development.”. The study can be seen as a microcosm of the development of biodegradable films for soils, which will help researchers quickly identify their general patterns. Readers can better understand the changes and development trends in this field in the past 30 years and provide references for future research.